SOSIALISASI PEMBUATAN ORGANIK CAIR BERBAHAN DASAR ECENG GONDOK - Rahmawati, Rina Dian; Aisa, Aufia; Khotimah, Khusnul; Mathoriyah, Lailatul; Choiruddin; Muhid, Muhammad Nur; Handayani, Putri; Masruroh, Siti Aisyatul; Hidayah, Leni Muliani; Ebwantoro, Jefry (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This activity aims to increase the awareness of the Tapen Village community regarding the importance of using water hyacinth plants as raw materials for making organic fertilizer, which is an innovative solution that not only helps overcome environmental problems, but also provides economic benefits. The approach method used for the community in Tapen village is the Participatory Action Research (PAR) method. This method is a research method carried out in a participatory manner between Farmer Groups to encourage the implementation of previously planned programs. This socialization activity was carried out through discussions in the form of providing materials and questions and answers regarding the importance of processing and using water hyacinth as a basic ingredient for liquid organic fertilizer. The results obtained from this activity are able to increase the knowledge and skills of the participants, especially farmer groups, village officials and Tapen Village youth in processing water hyacinth into liquid organic fertilizer. This output is very important because it empowers communities to utilize the natural resources around them, as well as reducing dependence on chemical fertilizers.